Effects of Homocysteine on Spontaneous Contractility of Pregnant Guinea-Pig Myometrium - Ayar, Ahmet; Tuğ, Niyazi; Çelik, Hüsnü; Özcan, Mete (Fırat University, 2001)
Objective: The aim of this study was to investigate the effects of homocysteine on spontaneous contractions of guinea pig myometrium. Material and method: Full thickness myometrium strips were obtained from late-pregnant guinea pigs following decapitation and suspended in an isolated organ bath which was filled with physiological salt solution at pH 7.4 maintained at 37°C and continuously bubbled with 95 CO2 %-%5 O2. After manifestation of spontaneous contractions under one gram of resting tension, homocysteine (0.2, 0.5 and 1 mM) was added to the organ bath and effects of this agent on frequency and amplitude of contractions were evaluated by 20-minute periods. One-way analysis of variance was used for statistical analysis of data. Results: Homocysteine caused increase in both frequency and amplitude of spontaneous contractions in a dose dependent manner. Conclusion: The results from this in vitro study indicates that, cardiovascular risk factor homocysteine has contracting pharmacological effects on guinea pig myometrium.

Amaç: Bu çalışmanın amacı, kobay miyometriyumunda spontan kontraksiyonlar üzerine homosisteinin etkilerini incelemektir. Gereç ve yöntem: İleri gebe kobaylar dekapitasyonla sakrifiye edildikten sonra Tüm katmanları içeren uterus şeritleri hazırlanarak içerisinde 37°C'de (pH 7.4) olan fizyolojik tuzlu su bulunan ve %95 CO2-%5 O2 gaz karışımı ile sürekli gazlandırılan izole organ banyosunda asıldı. Bir gramlık istirahat gerimi altında spontan kontraksiyonlar gözlendikten sonra organ banyosuna homosistein (0.2, 0.5 ve 1 mM) kümülatif olarak ilave edildi ve bu ajanın kasılmaların frekans ve genliği üzerine etkileri 20 dakikalık periyotlar halinde değerlendirildi. İstatistiksel değerlendirmelerde tek yönlü varyans analizi kullanıldı. Bulgular: Homosistein spontan kontraksiyonların frekans ve genliğinde doz bağımlı olarak artışa yol açtı. Sonuç: Bu in vitro çalışmanın sonuçları kardiyovasküler hastalıklar için bağımsız risk faktörü olan homosisteinin kobay miyometriyumunda kasılmaya yol açan farmakolojik etkisinin olduğunu göstermektedir.
HOMOSİSTEİNİN İZOLE GEBE KOBAY MİYOMETRİYUMUNDA SPONTANKASILMALAR ÜZERİNE ETKİSİ